Agreement Between Physical Therapists in Diagnosing Benign Paroxysmal Positional Vertigo. Issue 2 (April 2021) - Galgon, Anne K.; Tate, Angela; Fitzpatrick, Margaret; Schoenewald, Wendy Webb
Abstract : Background and Purpose: Individuals with benign paroxysmal positional vertigo (BPPV) are frequently referred to physical therapy for management, but little is known on how reliable therapists are at diagnosing BPPV. The purpose of the study was to examine the agreement between physical therapists in identifying nystagmus and diagnosing BPPV. Methods: Thirty-eight individuals with complaints of positional vertigo, 19 from each of 2 clinics (clinics 1 and 2) that specialize in vestibular rehabilitation, had eye movements recorded using video goggles during positioning tests including supine-to-sit, supine roll, and Dix-Hallpike tests. Three therapists from each of the clinics independently observed videos, documented nystagmus characteristics of each testing position, and made a diagnosis for each case. Kappa (κ) statistics were calculated between therapists within each clinic for nystagmus identification and diagnosis. Results: Clinic 1 therapists demonstrated substantial to almost perfect agreement in identifying nystagmus during positional tests (κ = 0.68-1, P < 0.005). Clinic 2 therapists showed moderate to almost perfect agreement for presence of nystagmus (κ = 0.57-1, P < 0.005). Therapists at both sites had almost perfect agreement of diagnosis side, canal, and mechanism (κ = 0.81-1, P < 0.005). Discussion and Conclusion: Therapists utilized observations from multiple positional tests to determine diagnoses. This was evident by occasional disagreement in nystagmus presence and characteristics, but agreement in diagnosis, including ruling out BPPV. The results may not be generalizable to all physical therapists or therapists' ability to diagnose central and atypical nystagmus presentations. Experienced physical therapists demonstrated strong agreement in diagnosing common forms of BPPV. Video Abstract available for more insight from the authors (see the Video Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A340 ). Abstract : Supplemental Digital Content is Available in the Text.